THE REORIENTATION OF THE UNITED KINGDOM’S FOREIGN POLICY TOWARDS THE INDO-PACIFIC: A NEOCLASSICAL REALIST ANALYSIS - Fajar Oktavianto; Pradono Budi Saputro; Muhammad Abdurrohim; Andina Mustika Ayu (Kajian Asia Pasifik, 2026)
This article analyzes the reorientation of the United Kingdom’s foreign policy towards the Indo-Pacific during 2021–2023. Gideon Rose’s neoclassical realism serves as the analytical framework, applying concepts of balance of power and domestic politics. This article argues that both domestic and regional systemic factors drive the foreign policy reorientation. It highlights how internal dynamics, particularly domestic politics, as well as external pressures such as geopolitical competition and security in the Indo-Pacific shape the United Kingdom’s strategic orientation. Employing an explanatory qualitative approach, this article integrates literature review and expert interviews to provide deeper insights into the United Kingdom’s foreign policy. The objective is to explain how domestic conditions and international structures interact to influence the reorientation of focus of the United Kingdom’s foreign policy. Research findings reveal that the United Kingdom seeks economic and trade opportunities in the Indo-Pacific while reinforcing its strategic position globally. Evidence of this policy reorientation appears in United Kingdom’s participation in alliances like AUKUS and in expanding economic cooperation with Indo-Pacific states.